Correction of functional capacity of myocardium in arterial hypertension associated with hyperuricemia and poikilocytosis comorbidities - Ye. L. Kovalenko; O. K. Melekhovets; V. F. Orlovskyi; Yu. V. Melekhovets (Zaporožskij Medicinskij Žurnal)
Aim. To study the influence of hyperuricemia (HU) on the functional capacity of the myocardium and erythrocytes morphology in patients with arterial hypertension (AH) and to estimate the possibility of their correction using low-level laser therapy (LLLT).